Earth-Fixed Books Reduce Motion Sickness When Reading With a Head-Mounted Display - Sato, Hikaru; Sato, Yuki; Takamatsu, Atsushi; Makita, Mitsuhiro; Wada, Takahiro (Frontiers in Virtual Reality, 2022)
There are concerns that viewing two-dimensional (2D) content such as web pages on a head-mounted display (HMD) in the car may aggravate motion sickness. This is because when 2D content is fixed to a head-fixed coordinate system, the appearance of the content does not change even when the body moves; therefore, it is impossible to visually perceive the movement of one’s body, resulting in a sensory conflict between the visual and vestibular senses. A method for reducing motion sickness when displaying 3D content on an HMD has been investigated; however, when displaying 2D content, no such method has been investigated. Therefore, this study aims to verify to the possibility of reducing motion sickness from the change of appearance caused by fixing 2D content to the earth-fixed coordinate system when viewing it with an HMD in a moving environment. Participants sat on a seat that was mounted on a vibrating device and moved in the pitch direction while reading a book on the HMD. Consequently, the severity of motion sickness was significantly lower when the book was fixed to the earth-fixed coordinate system than when fixed to the head-fixed coordinate system. This result suggests that by fixing the content to the earth-fixed coordinate system, motion sickness can be reduced because the movement of one’s body can be perceived through changes in the appearance of the content, and the sensory conflict between visual and vestibular sensations can be resolved.